Salvando a vida ou a si próprio: um comentário crítico ao fragmento 5 West, de Arquíloco (Nuntius Antiquus, 2008)
This paper tries to enrich a philological discussion regarding Archilocus' fragment 5 West. Textual criticism tradition has been arguing whether psykhén or autón should be taken into account in the beginning of the fragment's third line. Since our aim is to decide which term is more appropriate, relevant modern commentaries related to the subject and some Homeric passages have been consulted in order to support our arguments.